2010
DOI: 10.1002/chem.200901628
|View full text |Cite
|
Sign up to set email alerts
|

Universal Features of the Electron Density Distribution in Hydrogen‐Bonding Regions: A Comprehensive Study Involving H⋅⋅⋅X (X=H, C, N, O, F, S, Cl, π) Interactions

Abstract: Topological analyses of the theoretically calculated electron densities for a large set of 163 hydrogen-bonded complexes show that HX interactions can be classified in families according to X (X=atom or pi orbital). Each family is characterised by a set of intrinsic dependencies between the topological and energetic properties of the electron density at the hydrogen-bond critical point, as well as between each of them and the bonding distance. Comparing different atom-acceptor families, these dependencies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
124
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 239 publications
(185 citation statements)
references
References 38 publications
58
124
1
2
Order By: Relevance
“…According to this analysis, if the Coulombic repulsion can be corrected, even in ar ough way,w hat remains is qualitatively similart oan eutral complex, ar esult stronglys uggesting that hydrogenb onds between ions or neutralm olecules are not significantly different. This is in agreement with the topological analysiso ft he electron density, [25] where it is observed that the dependence of the topological properties at the critical points of the hydrogen bond with d H···O in ionic complexes are just as in neutral complexes, [26] ab ehavior previouslyo bserved in similar comparisons between ionic and neutral complexes. [9a] In the same sense, the NBO analysis shows that the energy stabilization, E(2), due to the charget ransfer from the lone pair of the carbonylg roup towards the s*O ÀHo rbital followst he same trend in the neutrala nd in the charged dimers (see Figure …”
Section: Energeticprofile Along the Dissociation Pathsupporting
confidence: 86%
“…According to this analysis, if the Coulombic repulsion can be corrected, even in ar ough way,w hat remains is qualitatively similart oan eutral complex, ar esult stronglys uggesting that hydrogenb onds between ions or neutralm olecules are not significantly different. This is in agreement with the topological analysiso ft he electron density, [25] where it is observed that the dependence of the topological properties at the critical points of the hydrogen bond with d H···O in ionic complexes are just as in neutral complexes, [26] ab ehavior previouslyo bserved in similar comparisons between ionic and neutral complexes. [9a] In the same sense, the NBO analysis shows that the energy stabilization, E(2), due to the charget ransfer from the lone pair of the carbonylg roup towards the s*O ÀHo rbital followst he same trend in the neutrala nd in the charged dimers (see Figure …”
Section: Energeticprofile Along the Dissociation Pathsupporting
confidence: 86%
“…Furthermore, the value of the Laplacian of electron density was observed to be positive for all the C-H···F's which showed that these exhibit closed shell character and for the contacts below 2.7 Å, such values were observed to lie above 0.578 e/Å 5 (which is the criterion for considering an interaction as a hydrogen bond [105,106]). Moreover, the value of |Vb|/Gb < 1 for all the ranges in R ij for H···F interactions was observed, which is an important criterion for H-bond, as suggested by Espinosa [110]. Finally with respect to the criteria constituted by IUPAC it was concluded that C-H···F interactions at short distances are a true "hydrogen bond".…”
Section: Why Fluorine Is So Special?mentioning
confidence: 80%
“…These relationships have been described earlier for similar interactions [16] and for different HBs. [45,46] Four types of chalcogen-chalcogen interactions have been observed. In these cases, the interatomic distance ranges from 2.93 to 5.62 , and exponential relationships similar to the HBs were found ( Figure 5).…”
Section: Discussionmentioning
confidence: 96%